2018
DOI: 10.1039/c8ta07028h
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium metal–rhodium oxide (Rh–Rh2O3) nanostructures with Pt-like or better activity towards hydrogen evolution and oxidation reactions (HER, HOR) in acid and base: correlating its HOR/HER activity with hydrogen binding energy and oxophilicity of the catalyst

Abstract: Rh–Rh2O3 nanostructures exhibit superior HER and HOR in acid and base; hydrogen binding energy and oxophilicity were found to be the equivalent descriptors for HER/HOR in alkaline medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 63 publications
3
82
0
Order By: Relevance
“…It can be seen that the percentage of P content is reduced when the upper potential limit becomes more positive (from 0.72 V to 1.12 V). Based on the literature about Rh‐Rh 2 O 3 used for catalyzing HER/HOR, the activity of partial oxidized catalyst (Rh‐Rh 2 O 3 ) is much better than that of Rh 2 O 3 ‐free Rh, we propose that in our Rh 2 P system, the decreased HOR activity is due the oxidation of P species when the upper potential limit becomes more positive. These results demonstrate the P plays an important role during the catalytic process for Rh 2 P/C, in line with those DFT calculations ,…”
Section: Figurementioning
confidence: 90%
“…It can be seen that the percentage of P content is reduced when the upper potential limit becomes more positive (from 0.72 V to 1.12 V). Based on the literature about Rh‐Rh 2 O 3 used for catalyzing HER/HOR, the activity of partial oxidized catalyst (Rh‐Rh 2 O 3 ) is much better than that of Rh 2 O 3 ‐free Rh, we propose that in our Rh 2 P system, the decreased HOR activity is due the oxidation of P species when the upper potential limit becomes more positive. These results demonstrate the P plays an important role during the catalytic process for Rh 2 P/C, in line with those DFT calculations ,…”
Section: Figurementioning
confidence: 90%
“…It is worth to highlight that the presence of the oxide was proposed to have a key role in efficient hydrogen evolution reaction by Rh/Rh 2 O 3 nanostructures bifunctional catalyst in alkaline environment, due to the favoured balancing of the surface properties coming from the weakening of hydrogen binding energy and the increase of oxophilicity and ability of OH À binding. 7 The electrochemical features of E-Rh/C and W-Rh/C (0.5 M H 2 SO 4 , 20 mV s À1 ) under argon saturated solution are similar, with an anodic wave at E pa ¼ 0.70 V vs. reversible hydrogen electrode (RHE), attributed to surface oxidation of metallic Rh to higher oxidation states, i.e. Rh(I)-Rh(III).…”
mentioning
confidence: 90%
“…[1][2][3][4] The development of Rh-based nano-catalysts has thus received increasing interest, also by virtue of their compelling properties towards electrocatalysis for energy applications, in particular for the hydrogen evolution reaction (HER). [5][6][7][8][9] To this purpose, Rh nanocrystals are oen obtained by solution-based routes, either one-pot or multi-step, in environments containing salts, carbohydrates, oil, hydrouoric acid or organic solvent, [6][7][8]10,11 by various procedures such as microwave heating, 1 solvothermal, 8 sonochemical 7 or electrochemical synthesis. 1 These methods allow the achievement of the conditions required for the conversion of Rh precursor (e.g., RhCl 3 , Na 3 RhCl 6 or Rh acetate) into metal nanocrystals, typically in the presence of stabilizing agents (oleylamine), strong reducing agents (NaBH 4 ) or high temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that optimized adsorption of hydroxyl species (OH*) could also promote the overall hydrogen oxidation rate in alkaline electrolytes . Indeed, a number of electrocatalyst systems consisting of two constituents (metals and/or metal oxides) have been reported with enhanced HOR performance with the secondary components showing optimal OH* binding, including Pt‐CeO 2 , Rh‐Rh 2 O 3 , PdNi, and PdCu . Nevertheless, these electrocatalyst systems typically contain platinum group metals (PGMs) and are thus not cost‐effective.…”
Section: Figurementioning
confidence: 99%